Edukasi pada Ibu Balita tentang Pemanfaatan Daun Kelor untuk Pencegahan Stunting di Desa Talang Bukit Muaro Jambi - Tuhu Perwitasari; Suci Rahmani Nurita; Armina Armina (Sekolah Tinggi Ilmu Kesehatan Baiturrahim Jambi, 2023)
Moringa leaves as an alternative local food to fulfill toddler nutrition in preventing stunting. Moringa is a plant that has not been fully utilized. The nutritional content of Moringa includes essential amino acids, excellent protein, phenolic amino acids, a source of vitamins and β-carotene. The target of this community service activity is mothers who have a total of 56 toddlers. There is still a lack of mother's knowledge about the use of Moringa leaves for stunting prevention. Providing health education that is carried out is about Education on the Utilization of Moringa Leaves for the prevention of stunting in Talang Bukit Village using demonstration and lecture methods through leaflet and power point media. After education there was an increase in knowledge of 68.75% about the use of Moringa leaves for stunting prevention.